The Feasibility of Cooperation to Comply with Land Use Change Obligations in the Marosszög Area of South Hungary - Ungvári, Gábor; Jolánkai, Zsolt; Kis, András; Kozma, Zsolt (Journal of Environmental Geography, 2018)
In many years excess water inundations generate a major obstacle to farming in the lowland part of Hungary, including the Marosszög area. Diverting water to large distances requires an infrastructure that is costly to develop and maintain. Alternatively, low-lying local land segments could be withdrawn from cultivation and utilized to collect the surplus water. The Ecological Focus Area (EFA) requirement of the EU points to the same direction: it requires that 5% of arable land is converted to other, ecologically more beneficial uses. During the research project it was tested if it is feasible to apply a novel economic policy instrument, an auction to trade land use change obligations, to achieve the EFA requirement in a cost effective way through the cooperation of farmers, while also creating a practical solution to manage the seasonal surplus water cover on land. The research was carried out in an interdisciplinary way: a dynamically coupled fully integrated hydrological model, including surface and subsurface modules, was applied by engineers to better understand the interconnections of land use, local hydrology and the role of the water diversion infrastructure; while a pilot auction exercise was conducted by economists with the participation of farmers to understand if cost reductions can be achieved through cooperation, as opposed to individual fulfilment of EFA obligations. The analysis also revealed which segments of the water diversion network are economic to maintain. It was confirmed that it is possible to improve local water management and satisfy the EFA requirements at a reduced cost if appropriate economic incentives are applied to trigger the cooperation of farmers.